Generalization of Fuzzy Soft BCK/BCI-Algebras - N. Alam; G. Muhiuddin; S. Obeidat; H. N. Zaidi; A. Altaleb; J. M. Aqib (Journal of Mathematics)
In this paper, the notions of ∈,∈∨q-fuzzy soft BCK/BCI-algebras and ∈,∈∨q-fuzzy soft sub-BCK/BCI-algebras are introduced, and related properties are investigated. Furthermore, relations between fuzzy soft BCK/BCI-algebras and ∈,∈∨q-fuzzy soft BCK/BCI-algebras are displayed. Moreover, conditions for an ∈,∈∨q-fuzzy soft BCK/BCI-algebra to be a fuzzy soft BCK/BCI-algebra are provided. Also, the union, the extended intersection, and the “AND”-operation of two ∈,∈∨q-fuzzy soft (sub-)BCK/BCI-algebras are discussed, and a characterization of an ∈,∈∨q-fuzzy soft BCK/BCI-algebra is established.